2005
DOI: 10.1007/s10764-005-2927-8
|View full text |Cite
|
Sign up to set email alerts
|

Postconflict Behavior Among Male Japanese Macaques

Abstract: Reconciliation was first described more than 20 years ago. Since then, it has been observed in many mammals (mainly primates) but data on postconflict behavior among males are still scarce because they usually aggressively compete for mating partners, rarely maintain amicable relationships with one another. Accordingly, reconciliation is expected to occur at low rates. Although this is true for Japanese macaque males, the subspecies on Yakushima Island (Macaca fuscata yakui) seems to represent an exception as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 55 publications
2
29
0
Order By: Relevance
“…Levels of certain behaviors deemed to represent certain components of relationship quality are also frequently employed, such as using agonistic support as a measure of relationship value. 71 Single behaviors, however, may not provide enough information for a true evaluation of the quality of the relationship between individuals, and the assignment of behaviors to particular components can be contentious, as for example, grooming has be used to represent either relationship value 80 or compatibility. 53,68 Thus, in order to gain more accurate, quantitative estimate of each of the relationship quality components, which is vital if the functions of bystander affiliation are to be fully understood, relationship quality must be measured using improved techniques.…”
Section: Measuring Relationship Qualitymentioning
confidence: 99%
“…Levels of certain behaviors deemed to represent certain components of relationship quality are also frequently employed, such as using agonistic support as a measure of relationship value. 71 Single behaviors, however, may not provide enough information for a true evaluation of the quality of the relationship between individuals, and the assignment of behaviors to particular components can be contentious, as for example, grooming has be used to represent either relationship value 80 or compatibility. 53,68 Thus, in order to gain more accurate, quantitative estimate of each of the relationship quality components, which is vital if the functions of bystander affiliation are to be fully understood, relationship quality must be measured using improved techniques.…”
Section: Measuring Relationship Qualitymentioning
confidence: 99%
“…The Assamese males of our study had a conciliatory tendency of 17.6%, which is within a tolerant range. Rhesus and Japanese macaque males generally have weak affiliative relationships; however, substantial intraspecific variation occurs in conciliatory tendencies of Japanese macaques (9.7-31%: Majolo et al 2005;Petit et al 1997;Schino et al 1998). Thus, one should take values from single groups with caution.…”
Section: Male Social Relationshipsmentioning
confidence: 99%
“…Majolo et al (2005) used amount of grooming as an assay of relationship quality for dyads of male Japanese macaques and found that conciliatory tendencies varied positively with the amount of grooming exchanged per dyad. Cooper et al (2005) showed that the proportion of conflicts reconciled by female dyads of Macaca assamensis varied positively with the amount of grooming and the number of coalitions per dyad.…”
Section: Empirical Evidence In Species Other Than Chimpanzeesmentioning
confidence: 99%